Peran Pendidikan Islam Dalam Melawan Radikalisme Melalui Moderasi Beragama - Agustin Sri Ningsih; Jumiarti Hurairah; Muji rahayu (4, 2024)
In Indonesia, Islamic education plays a crucial role in countering radicalism and promoting religious moderation. The Ministry of Religious Affairs emphasizes that religious education must be an integral part of the school curriculum, emphasizing a balance between intellectual and spiritual knowledge. This emphasis is increasingly relevant given the emergence of horizontal conflicts often triggered by radicalism and intolerance resulting from narrow and immoderate religious understandings. Islamic teachers and educators hold a significant responsibility in disseminating a correct understanding of key Islamic concepts, such as tolerance, jihad, and tawhid. A proper understanding will steer students away from extreme interpretations and direct them toward the teachings of Islam, which are a blessing for all. Research shows that inclusive character education can shape a young generation that values ​​multiculturalism and is accustomed to living in diversity with mutual respect. Madrasahs and Islamic boarding schools (pesantren) serve as Islamic educational institutions that play a crucial role in instilling moderate values. Through comprehensive learning, these institutions not only educate students in religious knowledge but also shape the morals and personalities of their students, making them more open and tolerant. However, to effectively address the challenge of radicalism, synergy is needed between educational institutions, parents, the community, and the government. Abstrak Di Indonesia, pendidikan Islam memiliki peran yang sangat penting dalam upaya melawan radikalisme sekaligus mempromosikan moderasi beragama. Kementerian Agama menegaskan bahwa pendidikan agama harus menjadi bagian integral dari kurikulum sekolah, dengan menekankan keseimbangan antara pengetahuan intelektual dan spiritual. Penekanan ini semakin relevan mengingat munculnya konflik horizontal yang sering dipicu oleh radikalisme dan intoleransi akibat pemahaman agama yang sempit dan tidak moderat.Guru dan pendidik Islam memegang tanggung jawab besar dalam menyebarkan pemahaman yang benar mengenai konsep-konsep kunci dalam Islam, seperti toleransi, jihad, dan tauhid. Pemahaman yang tepat akan menjauhkan peserta didik dari tafsir ekstrem sekaligus mengarahkan mereka pada ajaran Islam yang rahmatan lil ‘alamin. Hasil penelitian menunjukkan bahwa pendidikan karakter yang inklusif mampu membentuk generasi muda yang menghargai kehidupan multikultural serta terbiasa hidup dalam keberagaman dengan penuh sikap saling menghormati. Madrasah dan pesantren berfungsi sebagai lembaga pendidikan Islam yang berperan penting dalam menanamkan nilai-nilai moderat. Melalui pembelajaran yang komprehensif, kedua institusi ini tidak hanya mendidik dalam aspek pengetahuan agama, tetapi juga membentuk akhlak dan kepribadian santri agar lebih terbuka dan toleran. Namun, untuk menghadapi tantangan radikalisme secara efektif, diperlukan sinergi antara lembaga pendidikan, orang tua, masyarakat, dan pemerintah.